Implications of Constitutional Court Decision Number 135/PUU-XXII/2024 on the Separation of DPR and DPRD Elections on the Electoral System in Indonesia - Ernawati Huroiroh; Titik Triwulan Tutik; Dossy Iskandar Prasetyo (Universitas Muhammadiyah Surabaya, 2025)
Constitutional Court Decision Number 135/PUU-XXII/2024 regarding the separation of the DPR and DPRD elections marks a significant change in Indonesia's electoral system. Until now, the simultaneous implementation of elections using the “five boxes” model has caused various problems, including technical complexity in implementation, high logistical costs, and reduced attention to local issues. This study aims to analyze the constitutional implications and legal transition of the decision, particularly regarding the term of office of the DPRD, the potential for a vacuum in regional government, and the urgency of revising related laws. The research method used is normative legal research with a legislative approach and a conceptual approach through a review of the Constitutional Court's decision, the 1945 Constitution, the Election Law, the Regional Election Law, and relevant academic literature. The results of the study show that the separation of elections is intended to improve the effectiveness of their implementation, strengthen local democracy, and minimize the risk of administrative errors. However, this decision also poses challenges in the form of potential regulatory disharmony and constitutional uncertainty if it is not immediately followed by adjustments to legislation. Thus, this decision opens up space for electoral system reforms that are more responsive to local needs, but its success is highly dependent on the readiness of legislation and the governance of elections in Indonesia.